Legal Offerings Increase the Effectiveness of Determination of Coercive Money and Administrative Sanctions on State Administrative Decisions - Hamdalah, Mutiara; Arwana, Yudha Chandra; Yusrina, Asna (Universitas Negeri Semarang, 2021)
Legal Offers In Improving the Effectiveness of Forced Money Determination Efforts and Administrative Sanctions On the warning of a valid verdict that is not carried out by the defendant. The assessment of the formulation of the problem in this study is how the legal culture in Indonesia to the application of Article 116 paragraph (4) of Law No. 51 of 2009 on State Administrative Justice. In this paper the author also provides an understanding of the comparison of the State Administrative Law system (Indonesia) with Verwaltungsgerecht (Germany) in order to realize legal justice for the community. By using paradigms in terms of epistemological and axological aspects. In the implementation has not been found a special authority in overseeing the existence of the State Administrative Decision (KTUN) that has been validly decided by the judge, there are still some cases of defendants who do not carry out the warning of the verdict against the verdict. The defendant must pay forced money or administrative sanctions against it. From these cases, there should be special authority in supervising the KTUN that has been decided by the judge. The author in this paper offers a legal offer to improve the effectiveness in the implementation of the KTUN in improving legal certainty and guarantee of legal protection in the field of State Administrative Justice. The authors of this paper use descriptive doctrinal research methods, descriptive legal research that explains what should be communicated with the law in the review of das sollen and das sein.